The causality direction of the corporate social responsibility –corporate financial performance nexus: application of Panel Vector Autoregression approach - Lin, Woon Leong; Law, Siong Hook; Ho, Jo Ann; Sambasivan, Murali (Elsevier, 2019)
This study is an attempt to model the bidirectional linkages between corporate social responsibility (CSR) and corporate financial performance (CFP) by using the prospective and retrospective approaches. A panel data set for 100 of the Fortune Most Admired Companies was used to study the relationships. Moreover, 1000 firm-year observations were examined between the sample periods of 2007 and 2016. A new methodology known as Panel Vector Autoregression (Panel VAR) approach using the Generalised Method of Moments (GMM) was used in this study. The salient findings are: (1) better financial performance of firms lead to a better CSR engagement and (2) better CSR need not necessarily lead to superior CFP. A strong and substantial negative impact has been observed on CSR and the three CFP measures, namely, return on equity, return on assets, and return on invested capital. This finding has consistency with the trade-off hypothesis. This hypothesis posits that when firms are ‘‘being socially responsible’’, they will have a tendency to experience minimised shareholder wealth and lower profits, which restricts the socially responsible investments.